PKM Balanced Nutrition Education in Preventing Stunting In Adolescents - Zainal Munir; Cipta Frandy Pangestu 085258306128; Ageng Febriyan 085258306128; Muhammad Ali Asyur Shidqi4 085258306128; Aldo Ja’iz Maulana Hidayatullah 085258306128 (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2024)
A nutritional problem that still occurs and is a national nutrition problem is stunting. Stunting in toddlers is characterized by a short body size from their age accompanied by low cognitive ability. As a chronic nutritional problem, stunting occurs due to insufficient levels of nutrient consumption and has been going on for a long time. Stunting in toddlers will have both short-term and long-term impacts. Stunted people are very susceptible to diseases, the level of intelligence is below average and ultimately affects productivity. The long-term occurrence of stunting is the low quality of human resources and causes economic losses to the nation. The purpose of providing education and residents of MAN 1 Probolinggo that stunting prevention needs to involve educational institutions, because this is the root of the problem that needs to be given an understanding that efforts to reduce stunting must start from adolescents. Method Forms of education by means of counseling and delivery of material by lecture method. The implementation of educational activities as a topic in service activities is divided into 5 main stages, consisting of: Preparation Stage, Implementation Stage, Evaluation Stage, Role Division, Needs Analysis, Program Development, Program Implementation. Results: MAN 1 Probolinggo students received education from the concept of stunting and stunting prevention among parents who will become parents in the future.